Dime qué produces y te diré qué tan inequitativo eres: enfoque a la desigualdad colombiana. (2017)
The present investigative work, deepens into one of the biggest social problem of the called underdeveloped countries, based on the assumption that the productive structure of the departments in Colombia affects the way as the income from economic activities are distributed in the population. To test this hypothesis qualitative and quantitative evidence are presented, using different statistical methods to demonstrate that the Colombian departments that depends on the sector of agriculture, livestock, hunting, forestry and fishing, or mining or quarrying, have an income distribution more unequal than the rest of the departments. This inequality was measure using the Theil index, the index of Atkinson and the Gini coefficient, these in turn were calculated using the GDP per capita information of the departments and the capital Bogotá D.C., from the year 2000 to 2014. The different inequality measures used, allowed to see from different variables how the inequality is greater in those agriculture and mining departments. Also, through the causality test, it can be affirmed that the productive structure influences inequality.